Can search costs explain price differentiation in the Brazilian fund industry?: replicating Hortaçsu & Syverson (2004) - Soares, Paulo Sergio de Miranda da Costa (2017)
This work replicates Horta¸csu & Syverson (2004) model using Brazilian data. The objective of this paper is to evaluate if search frictions explain price dispersion, administrative fees, in the Brazilian funds industry. We use in our sample passive funds targeting two market indexes: Ibovespa and IRF-M. We found evidence that search costs are higher in the Ibovespa market than the IRF-M market. Considering those funds as differentiated products we observe that the Management Company plays an important role in consumers evaluation.